Hydrogen gas inhalation ameliorates glomerular enlargement after hypoxic-ischemic insult in asphyxiated piglet model - Takuma Iwaki; Shinji Nakamura; Takayuki Wakabayashi; Yasuhiro Nakao; Yinmon Htun; Toui Tsuchiya; Tsutomu Mitsuie; Kosuke Koyano; Aya Morimoto; Noriko Fuke; Takayuki Yokota; Sonoko Kondo; et al. (Scientific Reports)
Abstract Acute kidney injury (AKI) has been reported to occur in 30–70% of asphyxiated neonates. Hydrogen (H2) gas became a major research focus in neonatal medicine after the identification of its robust antioxidative properties. However, the ability of H2 gas to ameliorate AKI is unknown. We examined histopathological injuries in the piglet renal cortex on day 5 after a hypoxic-ischemic (HI) insult and if H2 gas can alleviate kidney injuries. Twenty piglets were divided into three groups: no insult (Control, n = 6), HI insult alone (HI, n = 8), and HI insult with H2 gas ventilation (HI-H2, 2.1–2.7% for 24 h, n = 6). The total glomerular cell count was significantly higher in the HI group than in the other groups, with no difference between the HI-H2 and control groups. Proximal tubular lumen narrowing was significantly increased in the HI group versus control, but not in the HI-H2 group. In this piglet model, glomerular enlargement with an increase in glomerular cell number due to tubular lumen narrowing was observed on day 5 after HI insult. H2 gas effectively suppressed this glomerular cell increase and tubular lumen narrowing.